2018
DOI: 10.1371/journal.pone.0201561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastroprotective and ulcer healing activities of yellow mombin juice from Spondias mombin L.

Abstract: Spondias mombin L. (yellow mombin) is a tree with a nutritional fruit that is commonly consumed in the North and Northeast of Brazil, as the juice of its pulp is rich in antioxidant compounds. This study aimed to investigate the gastroprotective and ulcer healing activities of yellow mombin juice (YMJ) in Wistar rats, and to elucidate the possible involved mechanisms. Phytochemical characterization of the lyophilized fruit juice was performed by high-performance liquid chromatography (HPLC). The gastroprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
3
11
0
2
Order By: Relevance
“…These results are in agreement with studies by [ 34 ], who demonstrated the safety of using S. mombin extracts in rodents.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with studies by [ 34 ], who demonstrated the safety of using S. mombin extracts in rodents.…”
Section: Resultssupporting
confidence: 93%
“…When administered intraduodenally, SmNE showed antisecretory activity, in which a reduction in the volume and weight of gastric content and an increase in pH can be observed, suggesting that antisecretory activity may contribute to the gastroprotection conferred to the extract. The results obtained corroborate those obtained by [ 34 ], in which the juice of the fruits of S. mombin —which is a 100% solution—also showed anti-secretory activity.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Todas as partes da árvore são de grande importância medicinal, a exemplo destacam-se os frutos e as folhas. Os frutos apresentam efeitos diuréticos (ELUFIOY et al, 2017), atividades gastroprotetoras e cicatrizantes de úlceras (BRITO et al, 2018). Já as folhas são apontadas por sua atividade contra o vírus da dengue (AJAEGBU et al, 2016), tratamento da doença de Alzheimer (ELUFIOYE et al, 2017), além de atividade antioxidante e anti-inflamatória (GOMES et al, 2020).…”
Section: Seriguelaunclassified
“…It is rich in carbohydrates (13.9 g/100 g), proteins (1.1 g/100 g), fibers (1.9 g/100 g), pro-vitamin A (223.0 RE/100 g), β-criptoxanthin (1708.5 μg/100 g), lutein (634.0 μg/100 g), zeinoxanthin (547.5 μg/ 100 g), β-carotene (314.0 μg/100 g), phenolic compounds (260.2 mg GAE/100 g), magnesium (15.1 mg/100 g), phosphorous (32.8 mg/100 g), potassium (288.3 mg/100 g) and calcium (11.0 mg/100 g) [19]. This unique composition has shown antioxidant effects [19], gastroprotective and ulcer healing activities [20], attenuation of ventricular remodeling after myocardial infarction [21], and cytotoxic effects on ovarian cancer cells [22].…”
Section: Introductionmentioning
confidence: 99%